2004
DOI: 10.1042/cs20030042
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genetic markers and the risk of restenosis after coronary angioplasty

Abstract: The aim of the present study was to test for possible associations between candidate gene polymorphisms and the risk of restenosis and recurrent restenosis after percutaneous transluminal coronary angioplasty (PTCA) without stenting. We followed up 511 PTCA patients, and restenosis and recurrent restenosis were defined according to angiographical criteria. Genotyping of the beta-fibrinogen -455 G/A, glycoprotein (GP) IIIa PlA1/PlA2, plasminogen activator inhibitor-1 (PAI-1) 4G/5G, factor V Leiden 1691 G/A, tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Lack of association was reported for this polymorphism in patients with coronary heart disease [20,30], and lack of association between the IL-1B-511 polymorphism and restenosis was reported in patients after coronary angioplasty [26,27] and balloon angioplasty [31]. To our knowledge, this is the first time that an association between IL-1B-511 polymorphism and the risk of developing restenosis after coronary stenting is analyzed considering the type of stent that was implanted (BMS or DES).…”
Section: Discussionmentioning
confidence: 94%
“…Lack of association was reported for this polymorphism in patients with coronary heart disease [20,30], and lack of association between the IL-1B-511 polymorphism and restenosis was reported in patients after coronary angioplasty [26,27] and balloon angioplasty [31]. To our knowledge, this is the first time that an association between IL-1B-511 polymorphism and the risk of developing restenosis after coronary stenting is analyzed considering the type of stent that was implanted (BMS or DES).…”
Section: Discussionmentioning
confidence: 94%
“…Factor V Leiden was associated in our study with protection against clinical restenosis. In a study by Volzke et al, 29 this association was not observed, but their study had limited statistical power and the genotype distribution of the Factor V Leiden polymorphism was not in Hardy-Weinberg equilibrium. The Factor V Leiden polymorphism is a well-known risk factor for venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…1.8. If correct, this puts the power of the study by Völzke et al [1] at the borderline for detection of such effects.…”
Section: Introductionmentioning
confidence: 92%
“…The authors [1] acknowledge that their study was powered to detect an odds ratio of 1.7-1.8 or greater for the effect of a given genetic polymorphism. Therefore we may ask ourselves whether we should expect a single polymorphism to have an effect of this size on such a complex disease, and whether knowing a patient's genotype will lead to a real benefit to the patient.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation